Do early father–infant interactions predict the onset of externalising behaviours in young children? Findings from a longitudinal cohort study. (19th July 2012) - Ramchandani, Paul G; Domoney, Jill; Sethna, Vaheshta; Psychogiou, Lamprini; Vlachos, Haido; Murray, Lynne
<x xml:space="preserve">Abstract</x> Background: Factors related to parents and parenting capacities are important predictors of the development of behavioural problems in children. Recently, there has been an increasing research focus in this field on the earliest years of life, however, relatively few studies have addressed the role of fathers, despite this appearing to be particularly pertinent to child behavioural development. This study aimed to examine whether father–infant interactions at age 3 months independently predicted child behavioural problems at 1 year of age. Method: A sample of 192 families was recruited from two maternity units in the United Kingdom. Father–infant interactions were assessed in the family home and coded using the Global Rating Scales. Child behaviour problems were assessed by maternal report. Hierarchical and logistic regression analyses were used to examine associations between father–infant interaction and the development of behavioural problems. Results: Disengaged and remote interactions between fathers and their infants were found to predict externalising behavioural problems at the age of 1 year. The children of the most disengaged fathers had an increased risk of developing early externalising behavioural problems [disengaged (nonintrusive) interactions – adjusted Odds Ratio 5.33 (95% Confidence Interval; 1.39, 20.40): remote interactions adj. OR 3.32 (0.92, 12.05)] Conclusions: Disengaged interactions of fathers with their infants, as early as the third month of life, predict early behavioural problems in children. These interactions may be critical factors to address, from a very early age in the child's life, and offer a potential opportunity for preventive intervention.